The Experience of Abortion: A Bibliographic Essay - Dollar, Disa G (PINS-Psychology in Society, 2026)
The recently changed legislative framework in South Africa has significant implications for research into abortion. Based on the World Bank Report on Women's Health, ARAG (Abortion Rights Action Group) (1995) estimates that 250 000 legal abortions will be performed yearly in South Africa. It Is likely that research into the experience of abortion will become a key research area. The legalisation of abortion on demand has occurred and research on the experience of abortion and all its implications Is vital for three main reasons. Firstly, the Choice on Termination of Pregnancy Act of 1996 promotes the provision of non-mandatory counselling, before and after abortions are performed. Thus health and social workers will need a theoretical framework for understanding the experience of abortion - in order to counsel women who are about to undergo, or who have just undergone, abortions. Providers of abortion services also need an understanding of how women experience abortion in order that they can provide sensitive services to minimize the distress of abortion. A second related point, is that psychotherapists will also require such a theoretical framework, as of the many hundreds of thousands of women who will now have legal abortions, many may seek psychotherapy to deal with their experience. Thirdly, there is a dearth of research on the experience of abortion in South Africa. Prior to the 1990s research into this issue was practically non-existent In South Africa (there are still no local Journal articles on the experience of abortion); but obviously the change in legislation on abortion will alter this. Taking into consideration that abortion has only very recently been legalised in South Africa (after decades of criminalisation and unremitting moral stricture, and amid considerable controversy) the finding that abortion is experienced differently in legal and illegal contexts (Gold-Steinberg, 1991) is crucial. Given South Africa's history, it is possible that abortion will be differently experienced here than in countries where it has long been legal.